Family Planning and Ethnic Heritage: Evidence from Sub-Saharan Africa - Graziella Bertocchi; Arcangelo Dimico; Chiara Falco (Institute of Labor Economics (IZA), 2024)
Family planning is a critical issue in countries, particularly those in sub-Saharan Africa, where high fertility rates coexist with low contraceptive use alongside adverse perinatal outcomes. Using a combination of ethnographic, ecological, and folklore data, we investigate the role played in this context by postpartum sexual abstinence, an extensively documented practice that, in preindustrial societies, nds its biological justication as a means to safeguard child survival. First, we show that the duration of contemporary postpartum abstinence increases with the duration of ancestral postpartum sex taboos within a woman's ethnic group. Second, postpartum abstinence is de facto pronatalist, as it increases the number of children ever born to a woman. At the same time, it increases the number of children of a woman who have died; lengthens birth intervals though not suciently to meet recommended guidelines; and increases neonatal death and child stunting. Exploring the underlying mechanisms reveals that postpartum abstinence is associated with patriarchal cultural norms and that the motivation for its adoption is that it serves as a purication ritual. Overall, our ndings question the biological rationale for postpartum abstinence as a means to protect child health, while aligning with anthropological evidence documenting its adoption as a ritual.
Keywords: J13; I18; N37; O11; D15; 330; family planning; postpartum abstinence; postpartum sex taboos; contraception; fertility; birth spacing; child health; tuber suitability; folklore; female empowerment; rituals; sub-Saharan Africa